Enhancing the Rheological Properties of Water-Based Drilling Fluid by Utilizing of Environmentally-Friendly Materials - Assi, Amel Habeeb; Haiawi, Ahmed Abdallah (Journal of Petroleum Research and Studies, 2021)
Recently, many materials have shown that they can be used as alternatives to chemicals materials in order to be used to improve the properties of drilling fluids. Some of these materials are banana peels and corn cobs which both are considered environmentally- friendly materials. The results of the X-ray diffraction examination have proved that the main components of these materials are cellulose and hemicellulose, which contribute greatly to the increasing of the effectiveness of these two materials. Due to their distinct composition, these two materials have improved the rheological properties (plastic viscosity and yield point) and reduced the filtration of the drilling fluids to a large extent. The addition rates used for each of the two materials (banana peels and corn cob) are 1%, 2%, 3%, 4%, 5% and 6%. As regard to banana peels, the results have shown that there is a direct correlation between the addition ratios, the increase in the rheological properties (plastic viscosity and yield point), and the decrease in filtration The corn cob has shown the same results. Also, 0.01% increase in the pH value was observed when adding a corn cob, while adding banana peels showed the opposite, as adding them led to 0.02% decrease in the pH value. Among the other properties that have been studied is density, as it has been noticed that there is no significant effect of these two materials on the density of drilling fluid. Moreover, the performance of these two materials has been compared with the PAC polymer. This research suggests that the possibility of moving towards corn cob and dried banana peels as additives for biodegradable drilling fluid. Apart from being environmentally friendly, the choice of using them is considered economically more efficient than other chemical additives. By all accounts, the above materials are an increasingly rational choice for moving forward for an environmentally friendly oil industry.